Effects of Heat and Mass Transfer on the Perfect Conducting Polar Fluid over a Stretching Sheet Due to Thermal Radiation (Advances in Applied Mathematics and Mechanics, 2010)
The objectives of the present study are to investigate the effectsof heat  and mass transfer on the unsteady flow of a perfectconducting polar fluid over a flat sheet with a linear velocity inthe presence of thermal radiation. Successive approximation methoddeveloped in Zakaria [Appl. Math. Comput. 10 (2002), Appl.Math. Comput. 155 (2005)] is adopted to solve the problem. Theeffects of Alfven velocity, mass transfer, various materialparameters, Prandtl number, Schmidt number and relaxation time onthe velocity, angular velocity, temperature and concentration arediscussed and illustrated graphically.